Theoretical Principles of Sociology, Volume 1 - Turner, Jonathan H. author. aut Link
XIX, 364 p.
Keywords: In a general study of Sociological Theory, social processes are usually broken down into three tiers: macrodynamics (societies and large-scale institutions), microdynamics (interpersonal encounters), and mesodynamics (corporations, communities, smaller organizations). In this seminal work, the author pulls these separate areas of research into one comprehensive general theory of social reality. More than analytical distinctions or research terminology, the author demonstrates that the social world actually unfolds along these three (macro, micro, and meso) levels of interaction. By developing a set of explanatory, testable, repeatable principles, the author creates a general empirical framework for sociological research. The three volumes of Principles of Sociology explore each level of social dynamics individually, with cross-references to bring the three together. This work will be essential for researchers in Sociological Theory and Social Psychology. Individual volumes will present new research of interest for researchers in Race and Ethnicity, Stratification, Demography, Political Sociology, Organizations and Community Movements, Motivation and Emotions. In this volume, the editor specifically focusses on macro-level dynamics and their impact on social interaction. Macro-level dynamics drive the formation of large-scale structures and their cultures.